Extractivismo e hidrocarburos no convencionales: el avance del fracking en el área natural protegida de Auca Mahuida (Neuquén, Argentina) - Acacio, Juan Antonio (Pontificia Universidad Católica del Perú, 2021)
This article aims to problematize the entry of the unconventional hydrocarbon activity that is carried out by means of the fracking technique, or hydrofracture, to the protected natural area of Auca Mahuida, in the province of Neuquén, Argentina. In order to account for the advance of extractivism in these peculiar territories, we take the case of Auca Mahuida’s analysis to investigate, with a strong descriptive and chronological component, in the way in which the state technical sectors in charge of the administration of these areas they problematized the entry of the Total Austral company into protected territory. We focus on the diagnoses and the links that they forged with the movement that sought to resist unconventional activity at the provincial level that began to develop strongly in 2013. In this key, we also realize the jump in scale of the conflict by getting involved the organization Friends of the Earth France, which carried out a reading in terms of north/south ecological debt regarding the activities of the French company.

Este artículo tiene como objetivo problematizar el ingreso de la actividad hidrocarburífera no convencional que se realiza mediante la técnica del fracking, o hidrofractura, al área natural protegida de Auca Mahuida, en la provincia de Neuquén, Argentina. Con el objetivo de dar cuenta del avance del extractivismo en estos territorios peculiares, tomamos el caso de análisis de Auca Mahuida para indagar, con un fuerte componente descriptivo y cronológico, en la forma en que los sectores técnicos estatales encargados de la administración de estas áreas problematizaron el ingreso de la empresa Total Austral en territorio protegido. Focalizamos en los diagnósticos y los vínculos que tejieron con el movimiento que buscaba resistir a nivel provincial a la actividad no convencional que comenzó a desarrollarse con fuerza a partir del año 2013. En esa clave, damos cuenta también del salto de escala del conflicto al involucrarse la organización Amigos de la Tierra Francia, que realizó una lectura en términos de deuda ecológica norte/sur respecto de las actividades de la empresa francesa.
Extractivism and unconventional hydrocarbons: the advance of fracking in the protected natural area of Auca Mahuida (Neuquén, Argentina)
Keywords: Ecological debt; Fracking; Hydrocarbons; Conservation; Deuda ecológica; Fracking; Hidrocarburos; Conservación; https://purl.org/pe-repo/ocde/ford#5.04.00